2022
DOI: 10.1111/jcpt.13769
|View full text |Cite
|
Sign up to set email alerts
|

14‐day famciclovir treatment significantly reduces the incidence of postherpetic neuralgia in elderly patients with herpes zoster

Abstract: What is known and objective: Pain is the main symptom of herpes zoster (HZ), whilst postherpetic neuralgia (PHN) is a long-term unbearable pain, which seriously affects the quality of life of patients and is also the most intractable problem for clinicians. Early antiviral treatment is considered as a key measure to reduce acute pain and PHN. Nevertheless, most patients still have long-term pain after 7 days of antiviral treatment, and some patients will develop PHN. This study aimed to investigate whether pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Studies have shown that famciclovir can effectively reduce acute pain and the incidence of PHN. While not a standard treatment for PTSD + AUD, viral infections like HSV may contribute to neuroinflammation and worsen psychiatric symptoms( 128 ). Famciclovir could be considered as an adjunctive treatment to address viral factors and improve mental health in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that famciclovir can effectively reduce acute pain and the incidence of PHN. While not a standard treatment for PTSD + AUD, viral infections like HSV may contribute to neuroinflammation and worsen psychiatric symptoms( 128 ). Famciclovir could be considered as an adjunctive treatment to address viral factors and improve mental health in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding rst-line antiviral therapy, famciclovir was prescribed most frequently (37%), followed by valaciclovir (36%) and acyclovir (19%). When compared with traditional 7-day antiviral therapy, a 14-day course of famciclovir can reduce PHN in elderly patients with HZ [102].…”
Section: Preventionmentioning
confidence: 99%